The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1063/1.4893335
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Hamilton-Jacobi separation in orthogonal coordinates with diagonal curvature

Abstract: We find all orthogonal metrics where the geodesic Hamilton-Jacobi equation separates and the Riemann curvature tensor satisfies a certain equation (called the diagonal curvature condition). All orthogonal metrics of constant curvature satisfy the diagonal curvature condition. The metrics we find either correspond to a Benenti system or are warped product metrics where the induced metric on the base manifold corresponds to a Benenti system. Furthermore we show that most metrics we find are characterized by conc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 9 publications
(37 reference statements)
0
25
0
Order By: Relevance
“…Bpζq " ζ 3 pζ´aq, B U K pζq " pζ´aq, ppζq " pζ´uqpζ´vqpζ´wq where u, v, w are the eigenfunctions of L. Application of equations (13) and (14) yield the transformation equations between pu, v, wq and pη, y, ξ, zq on H 3 and dS 3 , as appropriate. As usual, we write out the transformation equations below in terms of pseudo-Cartesian coordinates pt, x, y, zq associated with our null Cartesian coordinates pη, y, ξ, zq.…”
Section: Restriction To Hmentioning
confidence: 99%
“…Bpζq " ζ 3 pζ´aq, B U K pζq " pζ´aq, ppζq " pζ´uqpζ´vqpζ´wq where u, v, w are the eigenfunctions of L. Application of equations (13) and (14) yield the transformation equations between pu, v, wq and pη, y, ξ, zq on H 3 and dS 3 , as appropriate. As usual, we write out the transformation equations below in terms of pseudo-Cartesian coordinates pt, x, y, zq associated with our null Cartesian coordinates pη, y, ξ, zq.…”
Section: Restriction To Hmentioning
confidence: 99%
“…For simplicity we assume K has a single multidimensional eigenspace D. Then as in Section 4.2, the pair (D ⊥ , D) induces a warped product B × ρ F which is locally isometric to M . One can show that both B and F are spaces of constant curvature with B having the same curvature as M [35,Section 4].Then by Proposition 4.7, K induces a Killing tensor K F on F , by restriction. One can then recursively construct the KEM web by applying the above theorem to the ChKT K F on the space of constant curvature F , and then analyzing the resulting concircular tensor as above.…”
Section: Necessity Of Kem Webs In Spaces Of Constant Curvaturementioning
confidence: 99%
“…10 (separable webs in spaces of constant curvature[35]). In a space of constant curvature, every orthogonal separable web is a KEM web.…”
mentioning
confidence: 99%
“…Then there is a non-trivial concircular tensor L defined on M such that each eigenspace of K is L-invariant, i.e. L is diagonalized in coordinates adapted to the eigenspaces of K. ♦ A rigorous proof will be given in [RM14a]. In Riemannian spaces of constant curvature, this theorem can be proven by connecting the classification of separable metrics given by Kalnins and Miller in [Kal86] with Theorem 6.1.…”
mentioning
confidence: 99%
“…For a space of constant curvature with arbitrary signature, it can be shown that the classification given by Kalnins and Miller can be generalized in such a way that the separable metrics still satisfy the hypothesis of Theorem 6.1. This generalization will be given in [RM14a].…”
mentioning
confidence: 99%